THE EFFECT OF CORPORATE GOVERNANCE ON THE DISCLOSURE QUALITY OF NON-FINANCIAL INFORMATION IN INDONESIAN PUBLIC COMPANIES - Serly Serly; Apriliana Susanti (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study discusses the effect of profitability, company size, leverage, public ownership and type of auditor on the quality of financial statement disclosure of non-financial companies on the Indonesia Stock Exchange (IDX).Research population is companies in the Indonesia Stock Exchange in 2014-2018. The total population in the year of research was 627 companies and the samples that fit the criteria were 358 companies. Retrieval data was tested by using panel regression.From these results, it indicates the variable profitability have no significant on the quality of financial of financial statement disclosures (p=0,232 > 0,05). Company size has positive and significant effect on the quality of financial statement disclosures (p=0,002 < 0,05). Leverage does not significantly influence on the quality of financial statement disclosures (p=0,560 > 0,05). Community ownership does not significantly influence on the quality of financial statement disclosures (p=0,176 > 0,05). Type of auditor has positive and significant effect on the quality of financial statement disclosures (p=0,018 < 0,05).